AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Local temperature and ecological similarity drive distributional dynamics of tropical mammals worldwide - Lydia Beaudrot; Miguel A. Acevedo; Jean‐Philippe Lessard; Alex Zvoleff; Patrick A. Jansen; Douglas Sheil; Francesco Rovero; Timothy O’Brien; Eileen Larney; Christine Fletcher; Sandy Andelman; Jorge Ahumada (Global Ecology and Biogeography, 2019)
Aim Identifying the underlying drivers of species’ distributional dynamics is critical for predicting change and managing biological diversity. While anthropogenic factors such as climate change can affect species distributions through time, other naturally occurring ecological processes can also have an influence. Theory predicts that interactions between species can influence distributional dynamics, yet empirical evidence remains sparse. A powerful approach is to monitor and model local colonization and extinction—the processes that generate change in distributions over time—and to identify their abiotic and biotic associations. Intensive camera‐trap monitoring provides an opportunity to assess the role of temperature and species interactions in the colonization and extinction dynamics of tropical mammals, many of which are species of conservation concern. Using data from a pan‐tropical monitoring network, we examined how short‐term local temperature change and ecological similarity between species (a proxy for the strength of species interactions) influenced the processes that drive distributional shifts. Location Tropical forests worldwide. Time period 2007–2016. Major taxa studied Terrestrial mammals. Methods We used dynamic occupancy models to assess the influence of the abiotic and biotic environment on the distributional dynamics of 42 mammal populations from 36 species on 7 tropical elevation gradients around the world. Results Overall, temperature, ecological similarity, or both, were linked to colonization or extinction dynamics in 29 populations. For six species, the effect of temperature depended upon the local mammal community similarity. This result suggests that the way in which temperature influences local colonization and extinction dynamics depends on local mammal community composition. Main conclusions These results indicate that varying temperatures influence tropical mammal distributions in surprising ways and suggest that interactions between species mediate distributional dynamics.

The mammalian gene function resource: the international knockout mouse consortium - Allan Bradley; Konstantinos Anastassiadis; Abdelkader Ayadi; James F. Battey; Cindy Bell; Marie-Christine Birling; Joanna Bottomley; Steve D. Brown; Antje Bürger; Carol J. Bult; Wendy Bushell; Francis S. Collins; et al. (Mammalian Genome, 2012)